Pollution protest - Spartan Daily:::Creator::::::::::::
View of a student wearing a gas mask and holding two signs that read: Support your local smog center; Republican and Democrat Vote Redwood Support Senate Bill S. 2515 Smog doesn't bother me!! Who needs air???; Behind a table and umbrella are visible with the sign that reads: Stop Bay Fill. Other students are passing out pollution literature.